Professional Ethics Understanding and Professionalism Attitude of Prospective Make-Up Artist Students - Aisi Susanti; Rahmiati Rahmiati (Jurnal Locus Penelitian dan Pengabdian, 2026)
Rising demand for make-up artist (MUA) services has pushed clients to expect more than technical skill ethical, professional conduct now matters just as much. Yet a preliminary survey found that prospective MUAs often struggle with punctuality, client communication, and tool hygiene, prompting this inquiry into whether their grasp of professional ethics shapes how professionally they behave. Using a quantitative descriptive design, this study surveyed 124 Cosmetology and Beauty students (2022-2023 cohorts) at Universitas Negeri Padang, selected via the Slovin formula and proportionate stratified random sampling. A validated, reliable Likert questionnaire supplied the data, which were tested for normality and linearity before running simple linear regression, a t-test, and the coefficient of determination. Both variables scored in the good category (ethics understanding: M = 91.49, SD = 18.85; professionalism attitude: M = 62.38, SD = 12.90). Regression yielded Y = 15.845 + 0.509X (t = 12.266, p < .001), with ethics understanding explaining 55.2% of the variance in professionalism attitude (R² = .552) a significant, positive relationship that underscores the need for sustained ethics instruction in beauty vocational curricula.